Association of K121Q Polymorphism in Ectonucleotide Pyrophosphatase/Phosphodiesterase 1 with Clinical Characteristics of Metabolic Syndrom - Li, N.; Pan, H.; Cui, M.; Li, Q. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Purpose: This study aimed to investigate the relationships between K121Q polymorphism of ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) and clinical characteristics of metabolic syndrome (MS) in northern Han Chinese.Materials and Methods: A total of 209 MS patients and 248 healthy controls of Han ethnic group in northern China were enrolled in this study. Various clinical parameters of these participants were firstly collected and compared, including age, sex, body mass index (BMI), waist circumference (WC), systolic and diastolic blood pressures (SBP/DBP), fasting plasma glucose (FPG), fasting insulin (FINS), homeostasis model assessment of insulin resistance index (HOMA-IR), total cholesterol (TC), triglycerides (TG), high-density and low-density lipoprotein cholesterol (LDL-C/HDL-C). Then K121Q polymorphism of ENPP1 was determined by PCR and restriction enzyme digestion, and its relations with related clinical parameters were finally analyzed.Results: When compared with healthy controls, the age, BMI, WC, SBP, DBP, FPG, FINS, HOMA-IR, TC, TG and LDL-C were all significantly increased in MS patients (P<0.001). The allele frequencies of K and Q alleles in ENPP1 were 90.19% and 9.81% in MS patients, and 91.73% and 8.27% in healthy controls, respectively. Besides, only BMI and WC were significantly increased in MS patients carrying Q alleles (P<0.001), while no significant relations were found between K121Q polymorphism and other clinical parameters in either MS patients or healthy controls.Conclusion: The K121Q polymorphism of ENPP1 showed no direct correlation with MS, although it showed some correlation with BMI and WC in MS patients.
Keywords: ectonucleotide pyrophosphatase/phosphodiesterase 1; polymorphism; metabolic syndrome; obesity